(untitled) (Journal of Contemporary Issues in Accounting, 2023)
This study investigated the effect of electronic taxation on the performance of small and Medium Scale Enterprises in Awka, Anambra State. It sought to ascertain the effect of electronic taxation on the mortality rate of SMEs, on the tax filing costs of SMEs and to ascertain the effect of electronic taxation on multi taxation of SMEs in Awka, Anambra State. Survey research design was employed for the study. Questionnaires were distributed to Small and Medium Scale Enterprise operators in Awka South area of Anambra State to generate data for the study. Statistical analysis of the collected data was carried out with the aid of Stata Statistical Software Version 22. The result showed that electronic taxation significantly affects the mortality rate of SMEs in Awka, Anambra State, it also indicated that electronic taxation significantly affects the tax filing costs and on multi taxation of SMEs in Awka, Anambra State. It was concluded that electronic taxation plays a very significant role on the overall performance of Small and Medium Scale Enterprises in Awka, Anambra State. The study recommends that more SMEs operators should be enlightened on the need to adopt the E-tax system. While those already adopting the electronic tax system should take relevant security measures to protect their database.